CD155 Overexpression Correlates With Poor Prognosis in Primary Small Cell Carcinoma of the Esophagus - Zhao, Kaikai; Ma, Lin; Feng, Lei; Huang, Zhaoqin; Meng, Xiangjiao; Yu, Jinming (Frontiers in Molecular Biosciences, 2021)
CD155/TIGIT overexpression has been detected in various human malignancies; however, its expression status in primary small cell carcinoma of the esophagus (PSCCE) and its prognostic significance remain unclear. In this study, we aimed to explore the expression and prognostic value of CD155 and TIGIT in PSCCE. We detected CD155 and TIGIT expression in 114 cases of PSCCE using immunohistochemistry (IHC) and evaluated their relationship with the clinicopathological characteristics and survival of the patients. Survival analyses were performed using the Kaplan-Meier method and Cox proportional hazards model. Nomogram performance was assessed via the concordance index (C-index) and calibration plots. Decision curve analysis (DCA) was performed to evaluate the net benefit of the nomogram. We found that CD155 and TIGIT were overexpressed in PSCCE tissues, CD155 expression correlated positively with TIGIT (p < 0.001) and was significantly associated with tumor size, T stage, distant metastasis, TNM stage, and Ki-67 score. TIGIT expression was also significantly associated with T stage, distant metastasis, and TNM stage. Patients with high CD155 and TIGIT expression had a significantly shorter overall survival (OS) and progression-free survival (PFS), while the multivariate model showed that CD155 expression and the therapeutic strategy are independent prognostic factors for PSCCE. In the validation step, OS was shown to be well-calibrated (C-index = 0.724), and a satisfactory clinical utility was proven by DCA. In conclusion, our findings revealed that CD155 and TIGIT are highly expressed in patients with PSCCE and are associated with shorter OS and PFS, supporting their role as prognostic biomarker.